The company's financial performance in terms of liquidity and profitability - Noy, Ismail (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study analyzes PT Fastfood Indonesia, Tbk (KFC) 's financial condition through liquidity and profitability ratios. The goal is to evaluate the company's liquidity management and the efficiency of using assets and equity capital to generate profits. Research Design and Methodology: This study uses a quantitative descriptive design with secondary data from the financial statements of PT Fastfood Indonesia, Tbk (KFC). The analysis was carried out by calculating the current ratio, quick ratio, cash ratio, return on assets (ROA), and return on equity (ROE) and comparing them with industry standards. Findings and Discussion: The results show that the company's current ratio is poor, indicating potential difficulties in meeting short-term obligations. However, the quick ratio and cash ratio show sufficient liquidity. Regarding profitability, ROA indicates the efficient use of assets, while ROE suggests the company's inability to optimize equity capital to generate profits. Implications: These findings suggest improving the current ratio and ROE to improve financial stability. This study also contributes to the literature related to the financial performance of franchise companies, with suggestions for further research involving more companies and considering external factors.